PENGARUH ISCHEMIC COMPRESSION TERHADAP MYOFASCIAL PAIN SYNDROME OTOT UPPER TRAPEZIUS PADA SISWA DI SMPN 209 JAKARTA - Andreas Hariandja, Andy Martahan; Achwan, Achwan; Larasati, Diah Ayu (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Background: Myofascial pain syndrome (MPS) is a pain disorder characterized by sensory, motor and autonomic symptoms caused by trigger points. The international prevalence of myofascial pain syndrome is 13.5% to 47%, while in Indonesia the incidence of myofascial pain syndrome occurs as much as 54% in women and 45% in men. The purpose of this study was to determine the effect of ischemic compression on myofascial pain syndrome of the upper trapezius muscle in students at SMPN 209 Jakarta. Methods: This study used a pre experimental research with a one group pretest and posttest design. The sample consisted of 13 students at SMPN 209 Jakarta, selected by purposive sampling technique based on predetermined inclusion criteria. The measuring tool used is the Visual Analog Scale (VAS). Data analysis included univariate and bivariate analysis using the Wilcoxon test. Results: there was a change in the myofascial pain syndrome upper trapezius muscle pain scale of 4.08 from 5.46 to 1.38 with p-value = 0.001. Conclusion: Ischemic compression has a significant effect on reducing myofascial pain syndrome upper trapezius muscle pain.